Vineyard properties extraction combining UAS-based RGB imagery with elevation data. Issue 15 (18th August 2018) - Pádua, Luís; Marques, Pedro; Hruška, Jonáš; Adão, Telmo; Bessa, José; Sousa, António; Peres, Emanuel; Morais, Raul; Sousa, Joaquim J.
ABSTRACT: To differentiate between canopy and vegetation cover is particularly challenging. Nonetheless, it is pivotal in obtaining the exact crops' vegetation when using remote-sensing data. In this article, a method to automatically estimate and extract vineyards' canopy is proposed. It combines vegetation indices and digital elevation models – derived from high-resolution images, acquired using unmanned aerial vehicles – to differentiate between vines' canopy and inter-row vegetation cover. This enables the extraction of relevant information from a specific vineyard plot. The proposed method was applied to data acquired from some vineyards located in Portugal's north-eastern region, and the resulting parameters were validated. It proved to be an effective method when applied with consumer-grade sensors, carried by unmanned aerial vehicles. Moreover, it also proved to be a fast and efficient way to extract vineyard information, enabling vineyard plots mapping for precision viticulture management tasks.